Serotipe virus Dengue di Provinsi Aceh - Paisal Paisal; Reni Herman; Aya Yuriestia Arifin; Arie Ardiansyah; Sari Hanum; Khairiah Khairiah; Mukhlis Zuardi; Yasir Yasir (ASPIRATOR - Journal of Vector-borne Disease Studies, 2015)
WHO estimated 50 million dengue infections happen every year in the world. In Indonesia, there were 90,245 DHF cases on 2012 with 816 deaths. In the Province of Aceh, 2,269 cases happened in the same year. This study aimed to identify dengue virus serotype in Aceh. Sampling was done in Kota Banda Aceh Hospital, Kota Lhokseumawe Hospital, Kabupaten Aceh Tamiang Hospital, Kabupaten Aceh Barat Hospital, and Kabupaten Simeulue Hospital between May to December 2012. This was a clinical laboratory research with observation design using cross sectional approach. Research’s population was sample from patients with dengue clinical symptom. Using purposive sampling technique, we have collected 100 samples from the five hospitals (20 samples from each hospital). From RT-PCR, we found 16 positive samples (9 samples were DENV-4, 3 samples were DENV-1, 2 samples were DENV-2, and 2 samples were DENV-3.